NEW TRENDS AND MODERN APPROACHES TO FOREIGN LANGUAGE TEACHING (TEACHING UZBEK LANGUAGE FOR RUSSIAN GROUPS) (American Journal of Interdisciplinary Research and Development, 2023)
The relevance of this study is due to the fact that the introduction of new technologies in teaching foreign languages is one of the most important teacher tools that can help create not only a memorable lesson, but also an experience that will remain with students for a long time. The hypothesis of the study suggests that the use of target and project methods in teaching foreign languages can make the most of the language resources of students, allowing them to diversify their own learning. With the advent of information technology and related devices, the role of the teacher has changed significantly.